Cognitive-semantic types of Kalmyk proverbs - Ivanov, Eugene Eu. (The New Research of Tuva, 2024)
The article explores the cognitive semantics of Kalmyk proverbs from the perspective of categorizing their relationship to reality, as reflected in the proverbial worldview across empirical, axiological, ontological, and logical aspects. The research material consists of 312 proverbs from V. L. Kotvich's collection “Kalmyk Riddles and Proverbs” (1905).It is established that Kalmyk proverbs, in accordance with various aspects of their content's relation to reality, are differentiated into cognitive-semantic categories (types of proverbs): nomological and sentential (empirical aspect), truistic and gregarious (axiological aspect), paradoxical (logical aspect), and absurd (ontological aspect). Proverbs of different cognitive-semantic types exhibit varying quantitative representation (sentential ones being the most frequent and absurd ones the least), diverse logical-semantic structure (absurd and paradoxical proverbs more frequently determined logically and/or semantically, while others less so), varying conceptual-imagistic organization in terms of complexity (truistic, paradoxical, and absurd proverbs being the most intricate, while nomological ones are the least), and different degrees of ethno-cultural conditioning (sentential and absurd proverbs being more marked, while nomological and truistic ones are less so).
Keywords: paremiology; proverb; Kalmyk language; cognitive semantics; categorization of reality; cognitive-semantic type of proverb; ethno-cultural semantics